Current state of crowdsourcing taxonomy research: A systematic review - Aris, Hazleen (2017)
In this study, a systematic review was performed to identify the current state of crowdsourcing classification or taxonomy research to date. A total of 23 studies was found, which were categorised into general classification and specific classification, where specific classification was further divided into classification of processes, tasks and crowd. From these studies, a total of 21 attributes used in classifying crowdsourcing initiatives were found, which were categorised into seven themes as a result of constant comparison analysis.The seven themes are crowdsourcer, crowd, task, process, platform, content and reward. Expert evaluation involving five independent researchers in the area was used to validate the themes and the categorisation of the 21 attributes into the seven themes. Evaluation results showed that the independent researchers unanimously agreed on the seven themes and on the assignments made, after slight improvement on the latter.